2017
DOI: 10.1111/nph.14856
|View full text |Cite
|
Sign up to set email alerts
|

WRINKLED1 and ACYL‐COA:DIACYLGLYCEROL ACYLTRANSFERASE1 regulate tocochromanol metabolism in Arabidopsis

Abstract: SummaryPhotosynthetic organisms such as plants, algae and some cyanobacteria synthesize tocochromanols, a group of compounds that encompasses tocopherols and tocotrienols and that exhibits vitamin E activity in animals. While most vitamin E biosynthetic genes have been identified in plant genomes, regulatory genes controlling tocopherol accumulation are currently unknown.We isolated by forward genetics Arabidopsis enhanced vitamin E (eve) mutants that overaccumulate the classic tocopherols and plastochromanol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Furthermore, we found that natural variations in fatty acid pathway genes affect phenotypic variation in tocopherol content, which is supported by at least four points of evidence. The first was that five of the 32 genes affecting tocopherol content in AMP508 also showed a significant association with oil content in the same panel (Table S7), including DGAT, which has recently been shown to affect tocopherol content in Arabidopsis (Pellaud et al ., ). The second point of evidence was that the five genes that were significant for both oil and tocopherol were located within tocopherol QTLs, and one gene— DGAT —also fell within a QTL for oil content (Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, we found that natural variations in fatty acid pathway genes affect phenotypic variation in tocopherol content, which is supported by at least four points of evidence. The first was that five of the 32 genes affecting tocopherol content in AMP508 also showed a significant association with oil content in the same panel (Table S7), including DGAT, which has recently been shown to affect tocopherol content in Arabidopsis (Pellaud et al ., ). The second point of evidence was that the five genes that were significant for both oil and tocopherol were located within tocopherol QTLs, and one gene— DGAT —also fell within a QTL for oil content (Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, a mutation in LACS , a gene from the fatty acid metabolism pathway, resulted in an altered tocopherol profile (Figure ). Moreover, the influence of DGAT , another fatty acid pathway gene that was found to affect tocopherol content in this study, was recently shown to affect tocopherol content in Arabidopsis (Pellaud et al ., ). Together, these results suggest the existence of complicated cross‐talk between fatty acid and tocopherol metabolic pathways.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The tocomonoenol prenyl precursor THGGPP is an intermediate of the reductive pathway converting GGPP into PPP ( Kruk et al, 2011 ; Pellaud et al, 2018 ). This process is mediated by a geranylgeranyl reductase (GGR) that sequentially converts both geranylgeranylated chlorophyll a and GGPP into phytylated chlorophyll a and PPP, respectively ( Keller et al, 1998 ; Takahashi et al, 2014 ).…”
Section: Biosynthesis Of the Tocochromanol Isoprenoid Side Chainsmentioning
confidence: 99%
“…Tocochromanol biosynthesis is initiated by the condensation of two biosynthetic precursors, the polar homogentisate (HGA) and a lipophilic polyprenyl pyrophosphate that varies according to the type of tocochromanol. The polyprenyl precursor of tocopherols is phytyl pyrophosphate (PPP), geranylgeranyl pyrophosphate (GGPP) for tocotrienols, solanesyl pyrophosphate (SPP) for PC-8, and tetrahydrogeranylgeranyl pyrophosphate (THGGPP) for tocomonoenols ( Figure 1 ; Pellaud et al, 2018 ). The core tocochromanol biosynthetic pathway has been widely investigated and is now well-characterized ( Mène-Saffrané and DellaPenna, 2010 ; DellaPenna and Mène-Saffrané, 2011 ; Mène-Saffrané and Pellaud, 2017 ).…”
Section: Introductionmentioning
confidence: 99%